2020
DOI: 10.51791/njap.v46i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and serum biochemical indices of broiler chickens fed roselle seed (Hibiscus sabdariffa l.) cake based diet as replacement for soyabean meal

Abstract: Feeding trial experiment was carried out to evaluate the haematological and serum biochemical parameters of broiler chickens fed graded levels of Roselle Seed Cake (RSC) as replacement of a conventional protein source. Proximate composition was done to determine the nutrient content of RSC and experimental diets. The experiment contained graded levels of RSC replacing soya bean cake (SBC). One hundred and twenty (120) day old Ross broiler chickens were used in a Completely Randomized Design (CRD). The broiler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Lack of significant linear and quadratic effects in eosinophil and basophil concentrations implies that the broilers were protected against parasitic infections and intracellular bacteria to the same extent as those fed the control diets. Similarly, Olorede et al (1996) and Onunkwo et al (2019) reported a lack of adverse effects on haematological indices when broiler chickens were fed a 32% inclusion of Roselle seed cake and 10% palm kernel cake.…”
Section: Discussionmentioning
confidence: 91%
“…Lack of significant linear and quadratic effects in eosinophil and basophil concentrations implies that the broilers were protected against parasitic infections and intracellular bacteria to the same extent as those fed the control diets. Similarly, Olorede et al (1996) and Onunkwo et al (2019) reported a lack of adverse effects on haematological indices when broiler chickens were fed a 32% inclusion of Roselle seed cake and 10% palm kernel cake.…”
Section: Discussionmentioning
confidence: 91%
“…There was a detectable rise in the level of cholesterol between each experimental group and the control one. This increase in cholesterol levels might be due to the supplementation of SFM & RSM may enhance the fat content in the bird [11].Moreover; further investigations are needed to evaluate fat content in SFM & RSM. Similar to our findings, using 250 g/kg of SFM in the diets of broiler chicks harmed blood parameters [52].…”
Section: Discussionmentioning
confidence: 99%
“…It is not commonly used for human consumption, making it an economical and readily available resource. This characteristic also reduces the risk of potential scarcity [11]. RSM stands out as an outstanding alternate to soybean meal in broiler diets, considering various aspects such as economic feasibility, accessibility, nutritional value, and the bioavailability of its nutrients, particularly in terms of digestible protein and digestible energy [12].…”
Section: Introductionmentioning
confidence: 99%